Barriers and Bridges to Infection Prevention and Control on a Surgical Unit at a Netherlands Hospital and a Canadian Hospital: A Comparative Case Study Analysis. - Backman, Chantal; Marck, PB; Krogman, N (Université d'Ottawa | University of Ottawa, 2014)
Background: The overall aim of this research was to explore why some hospitals are more successful than others at reducing the acquisition rates of multidrug-resistant organisms (MDRO). Method: Using a socio-ecological perspective on health systems adapted from works in ecological restoration, ecosystems management, and healthcare, a participatory comparative case study design was employed. The study was conducted on a surgical unit at a Netherlands hospital with very low rates of MDRO and a surgical unit in a Canadian hospital with higher rates of these pathogens. Research methods included a total of six unit observations, nine practitioner-led photo walkabouts of the units (n=13), six focus groups (n=26), and the review of relevant policies and procedures. Results: When looking at the whole system for infection prevention and control in the context of particular environmental design constraints, and where hospital staff have reinforced norms of vigilance to prevent cross contamination, there were multiple conditions or activities at the Netherlands hospital that differed from the Canadian hospital which may have had an impact on the lower MDRO prevalence rates. These conditions or activities included differences in ratios of hospital beds per capita, bed occupancy rates, equipment cleaning processes in place, bed cleaning systems (centralized versus manual) and the presence of an active grassroots Hygiene in Practice group engaging practitioners in several ongoing activities to promote infection prevention and control. Conclusion: Given these clear differences between the two study sites, it is important to try to generate further evidence-informed rationale for these and other interventions in order to guide health system leaders who need to decide where to allocate finite resources.